PENGAMAN BRANKAS MENGGUNAKAN VOICE DENGAN MEDIA BLUETOOTH BERBASIS MIKROKONTRLLER ATMEGA 328 - Hani Dewi Ariessanti; Radiyanto Radiyanto; Afridha Septian Yuswanto (Universitas Raharja, 2015)
As the development of mobile technology which is not only used as telephone and text messages, but also can be used as a devices for controlling a safe. Such as a smarthphone that contained the computer’s features. So, the technology can be controlled remotely and according to what the user wants. Safe is a tool that is capable for helping human’s high risk work. That is why people make a safe for minimize the risk of crime and for securing, securing the valuable objects. Therefore, a safe’s security is designed by using motor servo as an output of the safe’s door movement,microcontroller as the brain, bluetooth as a communication media to send the data or input from the app, and android smartphone is taking role as a device which is contolling remotely the safe